Problems of flights safety control of civil aircrafts in Ukraine - Давиденко, М. Ф. (Proceedings of National Aviation University, 1998)
Solution of the problems of flight safety control is a complex character. Priority directions in solution of the problem is improvement of the system of the state regularity activity of all aviation system subjects including standards and recommended practice of international organization of civil aviation concerning safety of flights, increase of efficiency of measures directed at accident prevention, the human factor included. Each aviation company should have its own program of flight safety control